"Where Bert is or what Jane is doing", TUC leaflet 1941 (front) (1941)
1941 1939-1945 ""Where Bert is or what Jane is doing", TUC leaflet 1941 (front)" [HFR0064], 1941, Trades Union Congress This message from the TUC Chairman, George Gibson, warns war workers against gossip and careless talk which might leak defence secrets to enemy spies.